A boy with Silver–Russell syndrome and Sotos syndrome. Issue 2 (15th November 2020) - Schwaibold, Eva M. C.; Beygo, Jasmin; Obeid, Katharina; Jauch, Anna; Hinderhofer, Katrin; Moog, Ute
Abstract: Silver–Russell syndrome (SRS) is characterized by pre‐ and postnatal growth deficiency. It is most often caused by hypomethylation of the paternal imprinting center 1 of chromosome 11p15.5. In contrast, Sotos syndrome is an overgrowth syndrome that results either from pathogenic NSD1 gene variants or copy number variations affecting the NSD1 gene. Here, we report on a 6 month‐old boy with severe short stature, relative macrocephaly, severe feeding difficulties with underweight, muscular hypotonia, motor delay, medullary nephrocalcinosis, bilateral sensorineural hearing impairment and facial dysmorphisms. SNP array revealed a 2.1 Mb de novo interstitial deletion of 5q35.2q35.3 encompassing the NSD1 gene. As Sotos syndrome could not satisfactorily explain his symptoms, diagnostic testing for SRS was initiated. It demonstrated hypomethylation of the imprinting center 1 of chromosome 11p15.5 confirming the clinically suspected SRS. We compared the symptoms of our patient with the typical clinical features of individuals with SRS and Sotos syndrome, respectively. To our knowledge, this is the first study reporting the very unusual coincidence of both Sotos syndrome and SRS in the same patient.